Assessment of carbohydrate metabolism disorders in HIV-infected persons, patients with chronic hepatitis C and co-infection HIV/HCV - Iurko, K (Annals of Mechnikov’s Institute, 2020)
Introduction. Hepatitis C virus (HCV) and human immunodeficiency virus (HIV) are characterized by their wide distribution and ability to cause health disorders of the working population, thus causing significant morbidity and mortality worldwide. Ukraine - one of the countries of Europe, leads the sad rating of the number of identified HIV positive and AIDS cases and deaths from the disease. Chronic hepatitis C (CHC) is observed in 60-70% of HIV-infected individuals, due to the common modes of transmission of viruses. Co-infection with HIV/HCV is an important public health problem, since viruses, acting synergistically accelerate the progression of liver disease. HIV accelerates the progression of chronic hepatitis C to cirrhosis and hepatocellular carcinoma, thus increases "liver" mortality. This article discussed the state of carbohydrate metabolism in HIV-infected persons, patients with chronic hepatitis C and patients co-infected with HIV/HCV. Material & methods. The content of carbohydrate metabolism was determined in 107 patients: with chronic hepatitis C - 36 patients, with HIV infection - 35 and co-infection with HIV/HCV – 36 patients. Results. In the investigated patients identified carbohydrate metabolism disorders as an increase in serum glucose, insulin, glycosylated hemoglobin, level of insulin resistance. Glucose in patients of all groups was significantlly higher than in control subjects. For example, in HIV-infected persons, it was (5,16±0,11 mmol/l) in patients with chronic hepatitis C - 5,35±0,15 mmol/l, and in patients co-infected with HIV/HCV – 5,95±0,15 mmol/L. The insulin content was also increased in patients of all groups - in HIV-infected persons 9,26±0,24 MKOD/ml, in patients with chronic hepatitis C - 10,6±0,89 mU/L, and in patients co-infected with HIV/HCV - 11,9±0,81 MKOD / ml, respectively. HbA1C levels in HIV-infected individuals was 6,18±0,14 %, in patients with chronic hepatitis C - 6,36±0,13 %, and in patients co-infected with HIV/HCV - 7,05±0,15 %. These values were significantly higher than in the control group (5,74±0,17 %). HOMA-IR index in the studied patients was increased as compared with the control subjects, and in HIV-infected persons it was 2,51±0,21, in patients with chronic hepatitis C - 2,45±0,17 and co-infection with HIV/HCV - 3,16±0,24 respectively. The greatest manifestation of disorders of carbohydrate metabolism was in patients with established co-infection with HIV/HCV, and the lowest - in HIV-infected individuals. Conclusion. The most significant manifestations of disorders of carbohydrate and purine metabolism were observed in patients co-infected with HIV/HCV (t=20,5; p<0.001), that exceed a specified changes in patients with HCV 1,74 times (t=11,8; p<0.001) and HIV-infected patients (t=9,1; p<0.001) 2,25 times.